Forecasting Economic Indicators by Applied Technologies of Data Processing - R. R. Veynberg; A. S. Skotchenko; A. A. Grigorev; A. B. Yaroshyk (Вестник Российского экономического университета имени Г. В. Плеханова)
Today economic forecasts are necessary to identify possible goals of business and society development in general. Available models of information processes of economic system functioning differ by methods of mathematic tools usage. The degree of algorithm complexity with regard to their advantages and drawbacks cannot give an opportunity to choose one method without certain changes. For example, when the trend line is plotted usually only one economic indicator is used, however practice shows that in forecasting it is necessary to take into account several interdependent factors. Standard applied software products are rather expensive and to resolve the set tasks some additional instrumental means, tuning and users’ training are needed. The article proposes a method of plotting the trend line for several economic indicators simultaneously by using tools of widely spread software. The results of using the method for finding the common trend line for the rate of Euro to Russian ruble and the cost of oil barrel (3D) were shown. Apart from that the mathematic instrument for n-dimension case, which later could allow us to assess the possibility of changing several economic indicators at once and analyze their mutual impact.